Adjuvant chemotherapy in patients with locoregionally advanced nasopharyngeal carcinoma: Long-term results of a phase 3 multicentre randomised controlled trial. (April 2017) - Chen, Lei; Hu, Chao-Su; Chen, Xiao-Zhong; Hu, Guo-Qing; Cheng, Zhi-Bin; Sun, Yan; Li, Wei-Xiong; Chen, Yuan-Yuan; Xie, Fang-Yun; Liang, Shao-Bo; Chen, Yong; Xu, Ting-Ting; et al.
Abstract: Aim of the study: Previous results from our trial showed that adjuvant cisplatin and fluorouracil chemotherapy did not significantly improve survival after concurrent chemoradiotherapy (CCRT) in locoregionally advanced nasopharyngeal carcinoma (NPC) at 2 years. Here, we present the data of long-term survival and late toxicities to further assess the ultimate therapeutic index of adjuvant chemotherapy (AC). Methods: Patients with stage III–IVB (except T3-4N0) NPC were randomly assigned to receive CCRT plus AC or CCRT only at seven institutions in China. Patients in both groups received cisplatin 40 mg/m 2 weekly up to 7 weeks concurrently with radiotherapy. The CCRT plus AC group subsequently received adjuvant cisplatin 80 mg/m 2 and fluorouracil 800 mg/m 2 /d for 120 h every 4 weeks for three cycles. The primary end-point was failure-free survival. Results: Two hundred and fifty-one patients were randomised to the CCRT plus AC group and 257 to the CCRT only group. After a median follow-up of 68.4 months, estimated 5-year failure-free survival rate was 75% in the CCRT plus AC group and 71% in the CCRT only group (hazard ratio 0.88, 95% confidence interval 0.64–1.22; p = 0.45). 66 (27%) of 249 patients in the CCRT plus AC group and 53 (21%) of 254 patients in the CCRT only group developed one or more late grade 3–4 toxicities (p = 0.14). Conclusion: Adjuvant cisplatin and fluorouracil chemotherapy still failed to demonstrate significant survival benefit after CCRT in locoregionally advanced NPC based on the long-term follow-up data, and addition of adjuvant cisplatin and fluorouracil did not significantly increase late toxicities. Registration number: NCT00677118 . Highlights: Adjuvant chemotherapy did not reduce failure in nasopharyngeal cancer at 5 years. Adjuvant chemotherapy did not reduce death in nasopharyngeal cancer at 5 years. Adjuvant chemotherapy did not increase late toxicities in nasopharyngeal cancer.